Satisfaction of primary care physicians towards initiation of phone consultations during the COVID-19 pandemic management in Qatar: a cross-sectional study - Marwa Neshnash (12234704) (2022)
Objectives To assess primary care physicians’ satisfaction towards initiation of phone consultation during COVID-19 pandemic management in Qatar and to identify the factors associated with dis/satisfaction. Design A cross-sectional web-based survey was conducted from 1 June to 30 July 2020. Setting All the available 27 public primary healthcare centers in Qatar at the time of the study. Participants Two hundred ninety-four primary care physicians working in the publicly run primary healthcare corporation in Qatar. Primary outcome measures Overall satisfaction of primary care physicians with the initiation of phone consultation during the COVID-19 pandemic in Qatar and their satisfaction towards each aspect of this management. Results Two hundred thirty-nine primary care physicians participated in the survey with a response rate of 53.1%. Overall, about 45% and 21% of respondents agreed that COVID-19 disease management has highly impacted and very highly impacted their daily practice, respectively. More than half of the physicians (59.9%) indicated being satisfied/highly satisfied with the initiation of telephone consultation service. On the other hand, few physicians were satisfied (14.3%) or highly satisfied (3.4%) with conducting telephone consultations with patients who lack previous electronic medical records. Also, only 20.3% and 3.8% of physicians were satisfied and highly satisfied with the lack of physical examination in telephone consultations, respectively. On bivariate analysis, primary care physicians’ age was significantly associated with the perceived level of impact of COVID-19 management on daily practice (P = 0.03). There was no significant association between participants’ characteristics and the level of satisfaction toward telephone consultations. On the other hand, there was a statistically significant association between physicians’ age (p = 0.048) and gender (p = 0.014) and their level of satisfaction toward communication and support. Other Information Published in: BMC Primary Care License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12875-022-01654-6